The Impact of Emerging Technologies on Data Mining - Madukwe, Atkinson Ike; Madukwe, Jennifer Somtochukwu; Osonwa, Justina Ogochukwu; Ernest, Obiora Chukwuemerie (Asian Journal of Science and Applied Technology, 2021)
Business analytics has improved tremendously in recent past providing business leaders’ insights, particularly from operational data stored in transactional system. An example is e-commerce data analysis, which has recently come to be viewed as a killer appropriate for the field of data mining.